PENGARUH PENAMBAHAN GULA DAN KONSENTRASI STARTER KHAMIR TERHADAP KARAKTERISTIK WINE BUAH NAGA MERAH - Pratiwi, Rike; Wayan Gunam, Ida Bagus; Semadi Antara, Nyoman (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 2 (2019): JuniDO - 10.24843/JRMA.2019.v07.i02.p10, 2019)
The purpose of this research was to evaluate the influences of the sugar addition and the yeast starter concentration used in wine processing on the characteristic of red dragon fruit wine. The research was experimental research that designed using Randomized Block Design. Two factors were experimented, namely the sugar concentrations (22 o Brix, 25 o Brix and 28 o Brix) and yeast starter concentration (5%, 10% and 15%). The experiment was carried out in two block experiment, so that totally was done 18 unit. The result of this research showed that the interaction treatments of the addition of sugar and the addition of yeast starter concentration significantly affected the ethanol content, reducing sugar content and the total phenol of red dragon fruit wine. Otherwise, the interaction treatments did not significantly affect the total soluble solid and the acidity of the wine. The organoleptic test showed that the panelist prefered the wine which produced with 28 o Brix sugar content and the addition of 15% yeast starter. The etanol content, reducing sugar content, total soluble solid, pH and the phenol content of this wine were 11.24%; 1.756%; 12.10 o Brix; 3.75 and 1.637 mg/100 g, respectively. The methanol was not detected containing in the wine. Keyword :  sugar, yeast starter, red dragon fruit wine.